2012
DOI: 10.4236/jct.2012.325107
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Assessment of Ki-67 Expression on Core Needle Biopsy and the Surgical Specimens of Invasive Breast Cancer: Comparison of Local Pathologists’ Assessment and Central Review

Abstract: Purpose: The aim of this study was to assess the reliability of Ki-67 expression on core needle biopsy (CNB) and the surgical specimens of invasive breast cancer. We examined the concordance rate of Ki-67 expressions, hormone receptors, and human epidermal growth factor receptor 2 (HER2) status from a CNB with from a surgery in invasive breast cancer. Methods: A retrospective study was conducted on a clinical database of patients who underwent surgery for early breast cancer. Of these, 193 patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Our previous study analyzed 287 primary breast cancer patients who underwent preoperative CNB to compare the concordance rates for assessing Ki-67 status evaluated either by automated or central/local pathology assessment and showed that central review and the use of an automated analyzer can improve the accuracy of Ki-67 assessment. We then confirmed the necessity of a standardized evaluation method for Ki-67 expression in breast cancer to overcome the disadvantages of variable counting methods and measurement sites [23] [24].…”
Section: Discussionsupporting
confidence: 56%
“…Our previous study analyzed 287 primary breast cancer patients who underwent preoperative CNB to compare the concordance rates for assessing Ki-67 status evaluated either by automated or central/local pathology assessment and showed that central review and the use of an automated analyzer can improve the accuracy of Ki-67 assessment. We then confirmed the necessity of a standardized evaluation method for Ki-67 expression in breast cancer to overcome the disadvantages of variable counting methods and measurement sites [23] [24].…”
Section: Discussionsupporting
confidence: 56%
“…The core needle biopsy (CNB) procedure is almost as accurate as immunohistochemical analysis of surgical specimens for breast cancer diagnosis and is now widely accepted as the standard diagnostic procedure [17][18][19][20]. However, previous reports have shown variations in Ki-67 expression among pretreatment CNB specimens and post-treatment surgical specimens [21][22][23]. Therefore, it is important to consider potential discrepancies in Ki-67 values between CNB and surgical specimens, even in patients who receive no preoperative treatment, to standardize Ki-67 measurements in preoperative hormone therapy.…”
Section: Introductionmentioning
confidence: 98%
“…Equally in analytical validity, tumor heterogeneity and the lack of standard measuring method by pathologists may affect Ki67 measurement [11]. We had previously reported that these factors might affect the concordance rate for Ki-67 expression between CNB and surgical specimens, and we suggest that standardization of the measurement method by pathologists is most important [21]. However human observers spend considerable time and effort assessing large tissue areas and performing central reviews in general medical facilities which is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concordance rates of Ki-67 levels between core needle biopsy and postsurgical specimens have not been much investigated. Moreover, a few studies have reported that the concordance rates of Ki-67 between the two types of samples were lower than those for ER, PR, or HER2 expression [ 9 , 10 , 20 , 21 ]. However, the International Ki-67 in Breast Cancer Working Group commented on the type of biopsy and stated that both core and whole sections were suitable, although some data suggested that scores from whole sections might be higher than those from core biopsies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%